The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.aquatox.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of Manila clams Venerupis (=Ruditapes) philippinarum with varying parasite Perkinsus olseni burden to toxic algal Alexandrium ostenfeldii exposure

Abstract: Manila clam stock from Arcachon Bay, France, is declining, as is commercial harvest. To understand the role of environmental biotic interactions in this decrease, effects of a toxic dinoflagellate, Alexandrium ostenfeldii, which blooms regularly in Arcachon bay, and the interaction with perkinsosis on clam physiology were investigated. Manila clams from Arcachon Bay, with variable natural levels of perkinsosis, were exposed for seven days to a mix of the nutritious microalga T-Iso and the toxic dinoflagellate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 84 publications
(87 reference statements)
3
27
0
1
Order By: Relevance
“…Although immune defense against herpesvirus is not well documented, hemocyte-mediated responses appear to be involved, as shown by hemocyte infiltrations (Jenkins et al, 2013) and differentially expressed genes related to hemocyte functions in virus-infected oysters (Green et al, 2014;Jouaux et al, 2013;Renault et al, 2011). Previous studies showed an inflammatory response in bivalves exposed to Alexandrium sp., which increased circulating hemocyte concentration, as well as hemocyte infiltration and diapedesis, particularly in the digestive gland but also in the gills and the mantle (Galimany et al, 2008a;Haberkorn et al, 2010aHaberkorn et al, , 2010bLassudrie et al, 2014). More numerous hemocytes in these organs that are also targeted by OsHV-1 (Corbeil et al, 2015;Schikorski et al, 2011a) could result in a faster, more efficient defense and accelerate elimination of herpesvirus, possibly through release of humoral factors.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although immune defense against herpesvirus is not well documented, hemocyte-mediated responses appear to be involved, as shown by hemocyte infiltrations (Jenkins et al, 2013) and differentially expressed genes related to hemocyte functions in virus-infected oysters (Green et al, 2014;Jouaux et al, 2013;Renault et al, 2011). Previous studies showed an inflammatory response in bivalves exposed to Alexandrium sp., which increased circulating hemocyte concentration, as well as hemocyte infiltration and diapedesis, particularly in the digestive gland but also in the gills and the mantle (Galimany et al, 2008a;Haberkorn et al, 2010aHaberkorn et al, , 2010bLassudrie et al, 2014). More numerous hemocytes in these organs that are also targeted by OsHV-1 (Corbeil et al, 2015;Schikorski et al, 2011a) could result in a faster, more efficient defense and accelerate elimination of herpesvirus, possibly through release of humoral factors.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, exposure to Alexandrium spp. modulated antioxidant mechanisms (enzyme activity or gene expression) in clams and oysters (Estrada et al, 2007;Lassudrie et al, 2014;Romero-Geraldo and Herná ndez-Saavedra, 2012), and increased observations of ceroid bodies (containing oxidized molecules) in tissues (Galimany et al, 2008b;Lassudrie et al, 2014). Oxidation of the viral envelope could decrease virus viability, but also may alter entry mechanisms into the host cells, as well as interfering with viral replication (Lorizate and Krä usslich, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A positive effect of A. minutum exposure (depending upon the season and the oyster ploidy) or of toxin accumulation, however, was reported upon THC in C. gigas (Haberkorn et al, 2010a;Hégaret et al, 2007), possibly stimulating the immune system. Modifications of cellular proand anti-oxidant mechanisms, which may participate in the immune response and are involved in cellular protection, also have been reported (Fabioux et al, in preparation;Lassudrie et al, 2014). Whether or not these effects upon immune-related variables are direct consequences of Alexandrium sp.…”
Section: Introductionmentioning
confidence: 87%
“…exposure could not be assessed, because Alexandrium spp. also affect general physiological processes (Cucci et al, 1985;Shumway, 1988a, 1988b;Landsberg, 2002;Shumway, 1990) and tissue integrity (Galimany et al, 2008;Haberkorn et al, 2010b;Lassudrie et al, 2014;Medhioub et al, 2012), that could indirectly affect hemocytes.…”
Section: Introductionmentioning
confidence: 97%